Studies on the stimulation of Atlantic salmon macrophage-like cells with emphasis on respiratory burst - Ulvestad, Johanne Skår (UiT The Arctic University of Norway, 2017)
Reactive oxygen species (ROS) production in macrophage-like cells is induced as an antimicrobial defence against invading pathogens. In this present study, we have explored how different stimuli and metabolic inhibitors affects the level of respiratory burst in Atlantic salmon (Salmo salar L.) head kidney macrophage-like cells. Cells stimulated in vitro by bacterial lipopolysaccharide (LPS) and ß-glucan showed increased production of ROS compared to unstimulated cells. Both stimulation and co-stimulation by curdlan (ß-glucan) induced a higher production of ROS compared to stimulation and co-stimulation by LPS. Metabolic inhibitors (developed for mammals) co-incubated with the stimulants did not, in most cases, perturb the level of ROS generation in the salmon macrophage-like cells. The NAD+ content as well as the NAD+/NADH ratio increased in curdlan, and LPS + curdlan stimulated cells compared to control cells, which indicated increased metabolic activity in the stimulated cells. Supporting these findings, gene analysis using SYBR green real-time quantitative PCR showed that the genes Arignase-1 and IL-1ß were highly expressed in the stimulated cells.